Tungsten-tantalum-nickel-iron-cobalt alloy and preparation method and application thereof
By introducing tantalum and cobalt into tungsten-nickel ferroalloy and optimizing the sintering process, the problem of difficult to take into account the tensile strength and elongation of the existing tungsten alloy is solved, and a high-strength, high-elongation, tungsten-tantalum nickel-nickel ferrocobalt alloy is achieved.
Patent Information
- Application Number
- CN202411736874.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-21
AI Technical Summary
While improving the tensile strength, it is difficult to take into account high elongation, and the formation of tantalum hydrides leads to pores and reduces elongation.
The appropriate amount of tantalum and cobalt are introduced simultaneously in the W-Ni-Fe alloy, and prepared by powder metallurgy process, and the sintering process is optimized to improve the tensile strength and elongation of the alloy.
Tungsten tantalum nickel iron-cobalt alloy with tensile strength greater than 1260MPa and elongation greater than 30%, meeting the high demand for tungsten alloy strength in the military industry and national defense field.
Smart Images

Figure CN119491150A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a tungsten-tantalum-nickel-iron-cobalt alloy and a preparation method and application thereof, belonging to the technical field of tungsten heavy alloy preparation. Background Art
[0002] Tungsten has the advantages of high melting point, high density and good thermal conductivity. However, due to its intrinsic brittleness, pure tungsten has poor ductility, which limits its application prospects. In order to improve the brittleness of tungsten, researchers have introduced nickel-iron, nickel-copper and nickel-cobalt systems with better plasticity as bonding phases. During the liquid phase sintering process, tungsten particles are dispersed in the bonding phase, small particles are dissolved in the bonding phase, and then precipitated onto larger tungsten particles after saturation, which promotes the densification of tungsten alloys. Traditional tungsten alloys are represented by tungsten-nickel-iron and tungsten-nickel-copper systems. Compared with pure tungsten, the elongation is greatly improved, but its tensile strength is low. On this basis, the researchers further introduced other alloying elements to optimize the bonding phase composition to achieve the strengthening and toughening of tungsten alloys.
[0003] Tantalum is completely miscible with tungsten and dissolves well in the binder phase, which can effectively inhibit the dissolution of tungsten in the binder phase, thereby obtaining finer tungsten grains and playing a role in grain refinement. At the same time, the addition of an appropriate amount of tantalum can disperse in the binder phase to generate a nano-scale Ni3Ta second phase with strength equivalent to that of tungsten grains, thereby improving the strength of the tungsten alloy. However, in existing studies on tungsten alloys with tantalum addition, the formation of tantalum hydrides leads to the appearance of pores in the tungsten alloy, which greatly reduces the elongation.
[0004] Adding cobalt can improve the wettability of tungsten particles and the bonding phase in tungsten alloys, increase the interfacial bonding strength between tungsten particles and the bonding phase, and thus improve the tensile properties of the alloy. Related studies have shown that since the energy level on the cobalt 3d orbit is lower than that of iron, tungsten is easier to bond with cobalt, improving the electronic interaction between tungsten particles and the bonding phase, and effectively reducing the wetting angle between tungsten particles and the bonding phase. In addition, the addition of cobalt promotes the dissolution of tungsten in the bonding phase, and the increased volume fraction of the bonding phase is conducive to improving the elongation of the alloy.
[0005] At present, the research on the introduction of alloying elements into the bonding phase is usually based on a single element, such as rhenium, tantalum, molybdenum, cobalt, manganese, lanthanum and yttrium. However, when cobalt or tantalum is added alone to tungsten alloy, their mechanical properties are difficult to have both high tensile strength and total elongation. With the increase of tantalum content, although the tensile strength continues to increase, its elongation gradually decreases. With the decrease of cobalt content, its elongation gradually increases, but the tensile strength decreases. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention attempts for the first time to introduce an appropriate amount of tantalum and cobalt into the W-Ni-Fe alloy, and prepares a tungsten-tantalum-nickel-iron-cobalt alloy with a tensile strength greater than 1260 MPa and an elongation greater than 30% through a powder metallurgy process.
[0007] The invention discloses a tungsten-tantalum-nickel-iron-cobalt alloy to which cobalt and tantalum are added simultaneously, which has excellent mechanical properties and realizes simultaneous improvement of tensile strength and elongation of the tungsten alloy.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention discloses a tungsten-tantalum-nickel-iron-cobalt alloy, which is composed of tungsten, tantalum, cobalt, nickel and iron, and the mass ratio is tungsten: tantalum: nickel: iron: cobalt = 84-90: 1-10: 5.38-8.08: 2.31-3.46: 0.2-2. This certainly includes the scheme of tungsten: tantalum: nickel: iron: cobalt = 84-90: 1-5: 5.38-8.08: 2.31-3.46: 0.2-1.
[0010] Preferably, the present invention provides a tungsten-tantalum-nickel-iron-cobalt alloy composed of tungsten, tantalum, cobalt, nickel and iron, with the mass ratio of tungsten: tantalum: nickel: iron: cobalt = 85-87: 2.8-3.2: 6.8-7.2: 2.8-3.2: 0.2-1.
[0011] As a further preference, the present invention provides a tungsten-tantalum-nickel-iron-cobalt alloy, which is composed of tungsten, tantalum, cobalt, nickel and iron, and the mass ratio of tungsten: tantalum: nickel: iron: cobalt is 86~87:3:7:3:0.2~1.
[0012] As a further preferred embodiment, the tungsten-tantalum-nickel-iron-cobalt alloy of the present invention is composed of tungsten, tantalum, cobalt, nickel and iron, and the mass ratio of tungsten: tantalum: nickel: iron: cobalt is 86-87: 3: 7: 3: 0.6-1. This certainly includes the mass ratio of tungsten: tantalum: nickel: iron: cobalt is 86-87: 3: 7: 3: 0.8-1.
[0013] The invention discloses a method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy, comprising mixing tungsten powder, tantalum powder, cobalt powder, nickel powder and iron powder to obtain a mixed powder, pressing the mixed powder to obtain a compact, and sintering the compact in a vacuum environment to obtain the tungsten-tantalum-nickel-iron-cobalt alloy.
[0014] In the tungsten-tantalum-nickel-iron-cobalt alloy, the mass ratio of tungsten powder: tantalum powder: nickel powder: iron powder: cobalt powder is 84-90: 1-10: 5.38-8.08: 2.31-3.46: 0.2-2;
[0015] The sintering temperature is 1400-1500°C.
[0016] The preparation method of the present invention introduces an appropriate amount of tantalum and cooperates with other components to disperse and generate a fine Ni3Ta strengthening phase in the bonding phase to improve the tensile strength of the alloy. The inventors found that adding a trace amount of cobalt on this basis has little effect on the generation of the Ni3Ta strengthening phase, but under the synergistic effect of Ta and Co, it can significantly improve the wettability of the bonding phase and tungsten particles in the tungsten alloy. In addition, by optimizing the sintering process, the alloy can be sintered densely at 1400°C under the composition of the present invention, and at the same time, under the ratio of each component, a high-strength and high-elongation tungsten-tantalum-nickel-iron-cobalt alloy is finally obtained.
[0017] The inventors found that only by controlling the mass ratio of tantalum powder within the above range can more fine Ni3Ta strengthening phases be generated; if too much tantalum powder is added, the Ni3Ta phase will change from fine needles to coarse laths, and during the sintering process, the oxidation of tantalum will generate tantalum pentoxide particles, which hinder the flow of liquid phase during liquid phase sintering and cause brittle fracture of the alloy; and if too little tantalum powder is added, a certain amount of Ni3Ta phase cannot be generated in the matrix phase, and the strengthening effect on the alloy is not obvious.
[0018] The inventors found that the elongation of tungsten alloy can be effectively improved by controlling the mass ratio of cobalt powder within the above range; adding too much cobalt powder will cause the content of Ni3Ta strengthening phase to decrease or even disappear; while adding too little cobalt powder will not significantly improve the wettability of tungsten particles and bonding phase, and will not significantly improve the elongation of the alloy.
[0019] Preferably, the vacuum sintering temperature of the tungsten alloy is 1400-1500°C, more preferably 1420-1480°C, which of course includes 1450°C.
[0020] In a preferred embodiment, the mass ratio of tantalum to cobalt is 2 to 20, more preferably 3 to 15, which of course also includes 5.
[0021] In a preferred embodiment, the tungsten powder is a spherical powder with an average particle size of 3-5µm and a purity of ≥99.8%; the tantalum powder is a spherical powder with an average particle size of 25-35µm and a purity of ≥99.5%.
[0022] In a preferred embodiment, the nickel powder is a spherical powder with an average particle size of 3-5µm and a purity of ≥99.9%; the iron powder is a spherical powder with an average particle size of 3-5µm and a purity of ≥99.5%; and the cobalt powder is a spherical powder with an average particle size of 3-5µm and a purity of ≥99.8%.
[0023] The inventors found that higher powder purity can reduce the amount of impurity elements introduced into the alloy; spherical powder has the highest specific surface area at the same mass; fine powder can improve the sintering activity of the powder and increase the density of the alloy; but too small a powder particle size will increase the oxygen content of the powder, causing the alloy structure to deteriorate; tantalum is extremely easy to oxidize at high temperatures, especially tantalum powder after ball milling, which is extremely active. Although the use of fine tantalum powder can increase the sintering activity, it will cause an increase in the oxide content in the structure.
[0024] In a preferred embodiment, the mixing is performed in a three-dimensional mixer for 10-12 hours. A uniformly mixed tungsten, tantalum, nickel, iron and cobalt powder can be obtained by mixing in a three-dimensional mixer.
[0025] Preferably, the pressing method is cold isostatic pressing, and the pressure of the cold isostatic pressing is 250-300 MPa.
[0026] Preferably, the vacuum degree during sintering is ≤10 -3 Pa. Due to the high sensitivity of tantalum to oxygen, the vacuum degree needs to be strictly controlled during the sintering process of tungsten-tantalum-nickel-iron-cobalt alloy. The vacuum degree in the furnace is maintained at 10 -3 Below Pa, oxidation during sintering can be avoided.
[0027] The preferred solution is that the produced tungsten-tantalum-nickel-iron-cobalt alloy is mainly composed of tungsten particles and a bonding phase, the distribution ratio of the bonding phase is 30-35%, and the average particle size of the tungsten particles is ≦10 µm.
[0028] In a preferred embodiment, the tensile strength of the tungsten-tantalum-nickel-iron-cobalt alloy is ≧1200 MPa, preferably ≧1290 MPa, and the elongation is ≧25%, preferably ≧32%.
[0029] The tungsten-tantalum-nickel-iron-cobalt alloy prepared by the present invention has high strength and strong deformation ability, and the tensile strength is ≥1200 MPa. In the most preferred embodiment, the tensile strength is ≥1260 MPa, and the elongation is ≥32%, which can meet the extremely high demand for the strength and toughness of tungsten alloys in the military and national defense fields.
[0030] The present invention also provides an application of the tungsten-tantalum-nickel-iron-cobalt alloy prepared by the above preparation method. The tungsten-tantalum-nickel-iron-cobalt alloy can be applied to military weapons, aerospace, medical equipment, mold manufacturing and other fields.
[0031] Beneficial Effects
[0032] The present invention designs a tungsten-tantalum-nickel-iron-cobalt alloy with a strength greater than 1200 MPa and an elongation greater than 25% for the first time. The present invention realizes for the first time that after introducing an appropriate amount of tantalum and cobalt, a product with a tensile strength and elongation greater than that of the W-Fe-Ni basic alloy can be obtained. Through the synergistic effect of the preparation process and component optimization of the present invention, a high-quality product with a tensile strength of ≧1260 MPa and an elongation greater than 30% can be obtained.
[0033] The present invention optimizes the ingredient ratio, mixes tungsten powder, tantalum powder, nickel powder, iron powder and cobalt powder using a three-dimensional mixer, and presses them into shape using cold isostatic pressing; the designed alloy system adopts a two-step sintering method, and tantalum powder and cobalt powder are added at the same time to obtain a tungsten-tantalum-nickel-iron-cobalt alloy with high strength and high elongation.
[0034] In the new alloy system designed by the present invention, the addition of an appropriate amount of cobalt promotes the dissolution of tungsten in the matrix phase, increases the bonding phase, and improves the wettability of the bonding phase and tungsten particles; tantalum and nickel react at 1366°C to form a Ni3Ta strengthening phase; the sintering process is optimized, the sintering temperature is controlled at about 1450°C, and the generation of precipitated phases is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The original morphology of the tungsten element powder and tantalum element powder used in Example 1, wherein Figure 1 (a) is the morphology of tungsten powder. Figure 1 (b) is the morphology of tantalum powder;
[0036] Figure 2 The microstructures of the tungsten-nickel-iron alloy without tantalum and cobalt and the tungsten-tantalum-nickel-iron-cobalt alloy obtained in Examples 1-5 are: (a) is the microstructure of the tungsten-nickel-iron alloy without cobalt and tantalum; (b) is the microstructure of the tungsten-tantalum-nickel-iron-cobalt alloy with a cobalt mass fraction of 0.2%; (c) is the microstructure of the tungsten-tantalum-nickel-iron-cobalt alloy with a cobalt mass fraction of 0.4%; (d) is the microstructure of the tungsten-tantalum-nickel-iron-cobalt alloy with a cobalt mass fraction of 0.6%; (e) is the microstructure of the tungsten-tantalum-nickel-iron-cobalt alloy with a cobalt mass fraction of 0.8%; and (f) is the microstructure of the tungsten-tantalum-nickel-iron-cobalt alloy with a cobalt mass fraction of 1%.
[0037] Figure 3 The Ni3Ta phase in the tungsten-tantalum-nickel-iron-cobalt alloy is prepared by the method of Example 1.
[0038] Figure 4 The graph shows the test results of the dihedral angle between tungsten particles and bonding phases of tungsten-nickel-iron alloy without tantalum and cobalt and tungsten-tantalum-nickel-iron-cobalt alloy prepared by the methods of Examples 1, 2, 3, 4, and 5.
[0039] Figure 5The density and relative density change curves of the tungsten-nickel-iron alloy without tantalum and cobalt and the tungsten-tantalum-nickel-iron-cobalt alloy prepared by the methods of Examples 1, 2, 3, 4, and 5.
[0040] Figure 6 This is a tensile property test curve of the tungsten-tantalum-nickel-iron-cobalt alloy prepared by the method of Example 3.
[0041] As can be seen from FIG. 1 , the tungsten powder and tantalum powder used are spherical powders.
[0042] from Figure 2 It can be seen that the tungsten alloys prepared by the methods of Examples 1, 2, 3, 4, and 5 have a typical sintering neck structure during liquid phase sintering compared to the alloys without tantalum and cobalt, and the tungsten particles are obviously spheroidized and evenly distributed in the bonding phase.
[0043] from Figure 3 It can be seen that the gray needle-like Ni3Ta phase distributed in the bonding phase has a nanoscale size and has a good dispersion strengthening effect.
[0044] from Figure 4 It can be seen that the dihedral angles between the tungsten particles and the bonding phase in the tungsten-tantalum-nickel-iron-cobalt alloys prepared by the methods of Examples 1, 2, 3, 4, and 5 are all lower than those of the cobalt-free tungsten-tantalum-nickel-iron alloy prepared in Comparative Example 1, indicating that the addition of trace cobalt improves the wettability of the tungsten particles and the bonding phase in the tungsten alloy.
[0045] from Figure 5 It can be seen that, for the tungsten alloys prepared by the methods of Examples 1, 2, 3, 4, and 5, as the cobalt content increases, the actual density of the tungsten alloys decreases slightly, but the relative density is > 99%.
[0046] from Figure 6 The tensile strength and elongation of the products obtained after sintering process optimization and composition optimization are extremely superior. DETAILED DESCRIPTION
[0047] Example 1
[0048] A tungsten-tantalum-nickel-iron-cobalt alloy with a composition of 86.8W-3Ta-7Ni-3Fe-0.2Co, wherein the preparation method comprises the following steps:
[0049] Step 1: Mix the powder
[0050] Take 173.6 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%; 6 g of tantalum powder, with an average particle size of 30 microns and a purity greater than 99.5%; 14 g of nickel powder, with an average particle size of 3-5 microns and a purity greater than 99.9%; 6 g of iron powder, with an average particle size of 3-5 microns and a purity greater than 99.5%; 0.4 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The mass ratio of tantalum powder to cobalt powder is 15. Add 100 g of tungsten carbide balls with a ball diameter of 6 mm; seal the ball mill and pass high-purity argon gas, put all the above powders and tungsten carbide balls into a three-dimensional mixer, and mix for 10 hours.
[0051] Step 2: Green compact preparation process
[0052] After the mixing is completed, the materials are sieved to separate the tungsten carbide balls from the powder. The mixed powder is packed into a rubber sleeve and tightly sealed, and then put into a cold isostatic pressing furnace and pressed at a pressure of 250 MPa to obtain a compact.
[0053] Step 3: Sintering of Tungsten-Tantalum-Ni-Iron-Cobalt Alloy
[0054] The sintering process uses a vacuum sintering furnace; during the sintering process, the vacuum degree in the furnace is maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1450 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0055] The average density of tungsten-tantalum-nickel-iron-cobalt alloy is 16.97 g / cm 3 The average relative density is 99.39%, the average elongation is 26.47%, the average tensile strength is 1248.57MPa, the average grain size is 6.28 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 50.38°.
[0056] Example 2
[0057] A method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy with a composition of 86.6W-3Ta-7Ni-3Fe-0.4Co comprises the following steps:
[0058] Step 1: Mix the powder
[0059] Take 173.2 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%; 6 g of tantalum powder, with an average particle size of 30 microns and a purity greater than 99.5%; 14 g of nickel powder, with an average particle size of 3-5 microns and a purity greater than 99.9%; 6 g of iron powder, with an average particle size of 3-5 microns and a purity greater than 99.5%; 0.8 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The mass ratio of tantalum powder to cobalt powder is 7.5. Add 100 g of tungsten carbide balls with a ball diameter of 6 mm; seal the ball mill and pass high-purity argon gas, put all the above powders and tungsten carbide balls into a three-dimensional mixer, and mix for 10 hours.
[0060] Step 2: Green compact preparation process
[0061] After the mixing is completed, the materials are sieved to separate the tungsten carbide balls from the powder. The mixed powder is packed into a rubber sleeve and tightly sealed, and then put into a cold isostatic pressing furnace and pressed at a pressure of 250 MPa to obtain a compact.
[0062] Step 3: Sintering of Tungsten-Tantalum-Ni-Iron-Cobalt Alloy
[0063] The sintering process uses a vacuum sintering furnace; during the sintering process, the vacuum degree in the furnace is maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1450 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0064] The average density of tungsten-tantalum-nickel-iron-cobalt alloy is 16.93 g / cm 3 The average relative density is 99.37%, the average elongation is 26.83%, the average tensile strength is 1257.13 MPa, the average grain size is 7.03 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 45.05°.
[0065] Example 3
[0066] A method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy with a composition of 86.4W-3Ta-7Ni-3Fe-0.6Co comprises the following steps:
[0067] Step 1: Mix the powder
[0068] Take 172.8 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%; 6 g of tantalum powder, with an average particle size of 30 microns and a purity greater than 99.5%; 14 g of nickel powder, with an average particle size of 3-5 microns and a purity greater than 99.9%; 6 g of iron powder, with an average particle size of 3-5 microns and a purity greater than 99.5%; 1.2 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The mass ratio of tantalum powder to cobalt powder is 5. Add 100 g of tungsten carbide balls with a ball diameter of 6 mm; seal the ball mill and pass high-purity argon gas, put all the above powders and tungsten carbide balls into a three-dimensional mixer, and mix for 10 hours.
[0069] Step 2: Green compact preparation process
[0070] After the mixing is completed, the materials are sieved to separate the tungsten carbide balls from the powder. The mixed powder is packed into a rubber sleeve and tightly sealed, and then put into a cold isostatic pressing furnace and pressed at a pressure of 250 MPa to obtain a compact.
[0071] Step 3: Sintering of Tungsten-Tantalum-Ni-Iron-Cobalt Alloy
[0072] The sintering process uses a vacuum sintering furnace; during the sintering process, the vacuum degree in the furnace is maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1450 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0073] The average density of tungsten-tantalum-nickel-iron-cobalt alloy is 16.87 g / cm 3 The average relative density is 99.21%, the average elongation is 32.55%, the average tensile strength is 1268.82 MPa, the average grain size is 6.61 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 42.52°.
[0074] Example 4
[0075] A method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy with a composition of 86.2W-3Ta-7Ni-3Fe-0.8Co comprises the following steps:
[0076] Step 1: Mix the powder
[0077] Take 172.4 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%; 6 g of tantalum powder, with an average particle size of 30 microns and a purity greater than 99.5%; 14 g of nickel powder, with an average particle size of 3-5 microns and a purity greater than 99.9%; 6 g of iron powder, with an average particle size of 3-5 microns and a purity greater than 99.5%; 1.6 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The mass ratio of tantalum powder to cobalt powder is 3.75. Add 100 g of tungsten carbide balls with a ball diameter of 6 mm; seal the ball mill and pass high-purity argon gas, put all the above powders and tungsten carbide balls into a three-dimensional mixer, and mix for 10 hours.
[0078] Step 2: Green compact preparation process
[0079] After the mixing is completed, the materials are sieved to separate the tungsten carbide balls from the powder. The mixed powder is packed into a rubber sleeve and tightly sealed, and then put into a cold isostatic pressing furnace and pressed at a pressure of 250 MPa to obtain a compact.
[0080] Step 3: Sintering of Tungsten-Tantalum-Ni-Iron-Cobalt Alloy
[0081] The sintering process uses a vacuum sintering furnace; during the sintering process, the vacuum degree in the furnace is maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1450 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0082] The average density of tungsten-tantalum-nickel-iron-cobalt alloy is 16.84 g / cm 3 The average relative density is 99.28%, the average elongation is 30.69%, the average tensile strength is 1271.91 MPa, the average grain size is 6.24 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 49.68°.
[0083] Example 5
[0084] A method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy with a composition of 86W-3Ta-7Ni-3Fe-1Co comprises the following steps:
[0085] Step 1: Mix the powder
[0086] Take 172 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%; 6 g of tantalum powder, with an average particle size of 30 microns and a purity greater than 99.5%; 14 g of nickel powder, with an average particle size of 3-5 microns and a purity greater than 99.9%; 6 g of iron powder, with an average particle size of 3-5 microns and a purity greater than 99.5%; 2 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The mass ratio of tantalum powder to cobalt powder is 3. Add 100 g of tungsten carbide balls with a ball diameter of 6 mm; seal the ball mill and pass high-purity argon gas, put all the above powders and tungsten carbide balls into a three-dimensional mixer, and mix for 10 hours.
[0087] Step 2: Green compact preparation process
[0088] After the mixing is completed, the materials are sieved to separate the tungsten carbide balls from the powder. The mixed powder is packed into a rubber sleeve and tightly sealed, and then put into a cold isostatic pressing furnace and pressed at a pressure of 250 MPa to obtain a compact.
[0089] Step 3: Sintering of Tungsten-Tantalum-Ni-Iron-Cobalt Alloy
[0090] The sintering process uses a vacuum sintering furnace; during the sintering process, the vacuum degree in the furnace is maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1450 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0091] The average density of tungsten-tantalum-nickel-iron-cobalt alloy is 16.80 g / cm 3 The average relative density is 99.20%, the average elongation is 27.84%, the average tensile strength is 1293.51 MPa, the average grain size is 7.04 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 57.49°.
[0092] Comparative Example 1
[0093] The other conditions were the same as those in Example 1, except that the ratio of tungsten powder to cobalt powder was changed in the powder mixing step: 174 g of tungsten powder was taken, with an average particle size of 3-5 μm and a purity greater than 99.8%. No cobalt powder was added.
[0094] The average density of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 1 is 16.91 g / cm 3 The average relative density is 98.83%, the average elongation is 21.30%, the average tensile strength is 1185.11 MPa, the average grain size is 5.87 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 58.53°.
[0095] The inventors noticed that it is more complicated to directly measure the wetting angle between the bonding phase and the tungsten particles, so the dihedral angle is used to indirectly reflect the wettability of the tungsten particles and the bonding phase. The smaller the dihedral angle, the better the wettability of the bonding phase and the tungsten particles in the tungsten alloy. Comparative Example 1-5, no cobalt is added to Comparative Example 1, and its dihedral angle is larger, indicating that the wettability of the tungsten alloy and the bonding phase can be improved after adding an appropriate amount of cobalt. This is because the electrons on the 6s layer of tungsten atoms are unstable and easily transferred to orbits with lower energy, and the energy of the 3d layer of cobalt atoms is lower than that of iron. Tungsten is easier to bond with cobalt, improving the electronic interaction between tungsten particles and the bonding phase, which can effectively reduce the wetting angle between tungsten particles and the bonding phase.
[0096] Comparative Example 2
[0097] The other conditions are the same as those in Example 1, except that the ratio of tungsten powder to cobalt powder is changed in the powder mixing step: 168 g of tungsten powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. 6 g of cobalt powder, with an average particle size of 3-5 microns and a purity greater than 99.8%. The ratio of tantalum powder to cobalt powder is 1.
[0098] The average density of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 2 is 16.23 g / cm 3 The average relative density is 97.8%, the average elongation is 24.73%, the average tensile strength is 1081.49 MPa, the average grain size is 8.47 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 73.89°.
[0099] The inventors noted that after adding excessive Co, the Ni3Ta strengthening phase in the alloy gradually decreased, and after adding 3 wt.% Co, the strength and total elongation of the alloy were significantly reduced. This is because the ratio of tantalum powder to cobalt powder is too high, tantalum reacts with cobalt, and part of Ta is consumed. Excessive Co addition produces a significant increase in the solubility of W in the bonding phase, while the solubility of Ta in the bonding phase is significantly reduced, which inhibits the precipitation of the Ni3Ta strengthening phase in the bonding phase. In addition, compared to Examples 1-5, after adding excessive Co, the average size of the tungsten particles of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 2 increases, the WW connectivity increases significantly, and the dihedral angle between the bonding phase and the tungsten particles increases significantly, and the addition of excessive Co reduces the wettability of the bonding phase and the tungsten particles, and reduces the interface strength of the tungsten particles and the bonding phase.
[0100] Comparative Example 3
[0101] The other conditions were the same as those in Example 3, except that the temperature of the liquid phase sintering was changed in the sintering step: a vacuum sintering furnace was used in the sintering process; the vacuum degree in the furnace was maintained at 10 -3Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1380 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0102] The average density of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 3 is 16.81 g / cm 3 The average relative density is 98.85%, the average elongation is 27.37%, the average tensile strength is 1253.22 MPa, the average grain size is 6.63 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 53.06°.
[0103] The inventors noticed that, because the liquid phase sintering temperature was low in Comparative Example 3, the solubility of tungsten in the binder phase was low, and the amount of liquid phase was small, resulting in reduced wettability between the binder phase and the tungsten particles. The average dihedral angle between the tungsten particles and the binder phase in Comparative Example 3 was larger than that in Example 3, resulting in weakened interfacial bonding between the tungsten particles and the binder phase, and reduced strength and elongation.
[0104] Comparative Example 4
[0105] The other conditions were the same as those in Example 3, except that the temperature of the liquid phase sintering was changed in the sintering step: a vacuum sintering furnace was used in the sintering process; the vacuum degree in the furnace was maintained at 10 -3 Pa; first increase the temperature to 900 ℃ at 10 ℃ / min and keep it for 30 min; then increase the temperature to 1520 ℃ at 5 ℃ / min and keep it for 1.5 h; then cool down to room temperature at 10 ℃ / min and take out the sintered tungsten-tantalum-nickel-iron-cobalt alloy.
[0106] The average density of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 4 is 16.92 g / cm 3 The average relative density is 99.52%, the average elongation is 23.13%, the average tensile strength is 1220.02 MPa, the average grain size is 7.27 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 41.39°.
[0107] The inventors noticed that in Comparative Example 4, due to the high liquid phase sintering temperature, the wettability of the bonding phase and the tungsten particles was further improved, and the average dihedral angle was smaller than that of Example 3. However, due to the high sintering temperature, the connectivity of the tungsten particles increased, which promoted the combined growth of the tungsten particles, resulting in a significant increase in the size of the tungsten particles, and the alloy was prone to fracture along the tungsten-tungsten interface, and the tensile strength and total elongation were reduced.
[0108] Comparative Example 5
[0109] The other conditions are the same as those in Example 1, except that the proportion of tungsten powder is reduced in the powder mixing step. 159.68 g of tungsten powder is taken, with an average particle size of 3-5 microns and a purity greater than 99.8%; 9.23 g of tantalum powder is taken, with an average particle size of 30 microns and a purity greater than 99.5%; 21.54 g of nickel powder is taken, with an average particle size of 3-5 microns and a purity greater than 99.9%; 9.23 g of iron powder is taken, with an average particle size of 3-5 microns and a purity greater than 99.5%; and 0.32 g of cobalt powder is taken, with an average particle size of 3-5 microns and a purity greater than 99.8%.
[0110] The average density of the tungsten-tantalum-nickel-iron-cobalt alloy prepared in Comparative Example 5 is 16.21 g / cm 3 The average relative density is 99.63%, the average elongation is 27.57%, the average tensile strength is 1030.32 MPa, the average grain size is 8.79 microns, and the average dihedral angle between the bonding phase and the tungsten particles is 52.58°.
[0111] The inventors noticed that the tensile strength of the alloy was significantly reduced because the content of the W phase was reduced to 80% in Comparative Example 5. However, due to the increase in the bonding phase, the densification process during the liquid phase sintering process was more complete, the tungsten particles were evenly wrapped by the bonding phase, and the plasticity of the alloy was improved.
Claims
1. A tungsten-tantalum-nickel-iron-cobalt alloy, characterized in that: The tungsten-tantalum-nickel-iron-cobalt alloy is composed of tungsten, tantalum, cobalt, nickel and iron, and the mass ratio of tungsten: tantalum: nickel: iron: cobalt is 84-90: 1-10: 5.38-8.08: 2.31-3.46: 0.2-2.
2. A tungsten-tantalum-nickel-iron-cobalt alloy according to claim 1, characterized in that: In terms of mass ratio, tungsten: tantalum: nickel: iron: cobalt = 84-90: 1-5: 5.38-8.08: 2.31-3.46: 0.2-1; preferably, in terms of mass ratio, tungsten: tantalum: nickel: iron: cobalt = 85-87: 2.8-3.2: 6.8-7.2: 2.8-3.2: 0.2-1.
3. The tungsten-tantalum-nickel-iron-cobalt alloy according to claim 1, characterized in that: In terms of mass ratio, tantalum:cobalt = 2~20.
4. A method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy, characterized in that: Mixing tungsten powder, tantalum powder, cobalt powder, nickel powder and iron powder to obtain mixed powder, pressing the mixed powder to obtain a compact, and sintering in a vacuum environment to obtain a tungsten-tantalum-nickel-iron-cobalt alloy; In the tungsten-tantalum-nickel-iron-cobalt alloy, the mass ratio of tungsten powder: tantalum powder: nickel powder: iron powder: cobalt powder is 84-90: 1-10: 5.38-8.08: 2.31-3.46: 0.2-2; The sintering temperature is 1400-1500°C.
5. The method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy according to claim 4, characterized in that: The vacuum sintering temperature of tungsten alloy is 1420-1480°C, more preferably 1450°C.
6. The method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy according to claim 4, characterized in that: The tungsten powder is a spherical powder with an average particle size of 3-5µm and a purity of ≥99.8%; the tantalum powder is a spherical powder with an average particle size of 25-35µm and a purity of ≥99.5%.
7. The method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy according to claim 4, characterized in that: The nickel powder is a spherical powder with an average particle size of 3-5µm and a purity of ≧99.9%; the iron powder is a spherical powder with an average particle size of 3-5µm and a purity of ≧99.5%; the cobalt powder is a spherical powder with an average particle size of 3-5µm and a purity of ≧99.8%.
8. The method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy according to claim 4, characterized in that: The mixing is carried out in a three-dimensional mixer, and the mixing time is 10-12 hours; The pressing method is cold isostatic pressing, and the pressure of cold isostatic pressing is 250-300 MPa; The vacuum degree during sintering is ≤10 -3 Pa.
9. The method for preparing a tungsten-tantalum-nickel-iron-cobalt alloy according to claim 5, characterized in that: The tensile strength of the tungsten-tantalum-nickel-iron-cobalt alloy is ≧1200 MPa, preferably ≧1290 MPa, and the elongation is ≧25%, preferably ≧32%.
10. An application of the tungsten-tantalum-nickel-iron-cobalt alloy according to any one of claims 1 to 3, characterized in that: The application fields of the tungsten-tantalum-nickel-iron-cobalt alloy include at least one of military weapons, aerospace, medical equipment, mold manufacturing and other fields.
Citation Information
Cited By
Double-phase deeply-alloyed alloy tungsten and preparation method thereof
CN120608228A